Pilot Investigation of a Virtual Gastric Band Hypnotherapy Intervention. Issue 4 (1st October 2016) - Greetham, Stephanie; Goodwin, Sarah; Wells, Liz; Whitham, Claire; Jones, Huw; Rigby, Alan; Sathyapalan, Thozhukat; Reid, Marie; Atkin, Stephen
Abstract: This 24-week-long pilot investigation of 30 men and women with a BMI > 27 kg/m 2 aimed to determine whether virtual gastric band (VGB) hypnotherapy has an effect on weight loss in overweight adults, compared to relaxation hypnotherapy and a self-directed diet. Levels of weight loss and gain ranged from −17 kg to +4.7 kg in the VGB hypnotherapy group and −9.3 kg to +7.8 kg in the relaxation group. There was no significant difference between VGB hypnotherapy as a main effect on weight loss, (X 2 = 0.67, p = .41, df = 1) and there was no evidence of differential weight loss over time, (X 2 = 4.2, p = .64, df = 6). Therefore, the authors conclude that there was no significant difference between VGB hypnotherapy and the relaxation hypnotherapy.